2017
DOI: 10.3920/wmj2017.2188
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect ofAspergillus awamori on aflatoxin B1-induced hepatic damage in rabbits

Abstract: This study was conducted to investigate the effect of dietary supplementation of Aspergillus awamori on aflatoxin B1 (AFB1)-induced liver damage in rabbits. Administration of AFB1 (0.3 mg/kg diet) led to a significant reduction in body weight, body weight gain, total feed intake, total serum proteins, albumin, high density lipoprotein-cholesterol, phagocytic activity, phagocytic index, and the antioxidant enzyme, glutathione peroxidase (GPx). Moreover, AFB1 administration was associated with a significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…In line with the present study, Abdelhady et al. (2017) reported that A. awamori generated increased antioxidative status in rabbits through upregulating the antioxidative‐related genes.…”
Section: Discussionsupporting
confidence: 92%
“…In line with the present study, Abdelhady et al. (2017) reported that A. awamori generated increased antioxidative status in rabbits through upregulating the antioxidative‐related genes.…”
Section: Discussionsupporting
confidence: 92%
“…Liver damage constitutes one of the main causes of hepatocellular carcinoma (HCC) that leads to death worldwide 1 3 . Hepatitis is one of earlier signs of liver damage, which is characterized by inflammatory cells infiltration, congestion of blood vessels, and cellular degenerative changes.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis is one of earlier signs of liver damage, which is characterized by inflammatory cells infiltration, congestion of blood vessels, and cellular degenerative changes. Hepatitis could be induced by a viral infection, microbial metabolites, metabolic and autoimmune diseases, environmental toxicants, and alcohol and drug abuse 1 , 3 , 4 . If hepatitis was left for a long time without suitable treatments, other complicated liver disorders such as fibrosis and cirrhosis would be developed and in advanced cases become risk factors for HCC 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit's industry plays an important role in Egypt economic development, as it provides high-quality flesh which is characterized by less fat, easily digestible, and higher nutritional value. Rabbits contribute to fur production and were used for the production of antibodies and antisera using in different research aspects (Abdelhady et al, 2017, Gaber, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants are extensively used nowadays in the treatment of many diseases (Elgazar et al, 2018;Choi et al, 2011;Selim et al, 2019). Medicinal herbal plants, such as Echinacea, curcumin, garlic, onion, ginger, and astragalus, are used as immunomodulators (Abu Khudir et al, 2019;El-Magd et al, 2017;Sharma et al, 2017). Echinacea purpurea is a medicinal herb that contains phytochemicals such as polysaccharides, flavonoids, caffeic acid derivatives (chicoric acid), essential oils, polyacetylenes, and alkyl amides, with a particular immunostimulatory effect for polysaccharides and chicoric acid (Manayi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%